2021
DOI: 10.1177/00033197211050446
|View full text |Cite
|
Sign up to set email alerts
|

Can Serum Endocan Levels be Used as an Early Prognostic Marker for Endothelial Dysfunction in COVID-19?

Abstract: In this study, we aimed to investigate whether degree of pneumonia and COVID-19 prognosis are associated with serum endocan levels at the early stage, when vascular damage has started. Patients between the ages of 18–85 years who were hospitalized and followed up with a diagnosis of COVID-19 were included in the study. A total of 80 patients were divided into 2 groups as mild/moderate pneumonia and severe pneumonia. Serum endocan levels were measured on the 8th day from the onset of symptoms in all patients. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…This finding was in line with the study of Medetalibeyoglu et al, even if endocan was not assayed with the same kit [ 20 ]. Very recently, a few studies reported the potential interest of serum endocan in the prognosis of COVID-19 [ 21 , 22 , 23 ]. These studies focused on endocan’s ability to predict mortality [ 21 ] and to distinguish moderate from severe degrees of pneumonia [ 22 , 23 ], with different conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This finding was in line with the study of Medetalibeyoglu et al, even if endocan was not assayed with the same kit [ 20 ]. Very recently, a few studies reported the potential interest of serum endocan in the prognosis of COVID-19 [ 21 , 22 , 23 ]. These studies focused on endocan’s ability to predict mortality [ 21 ] and to distinguish moderate from severe degrees of pneumonia [ 22 , 23 ], with different conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, a few studies reported the potential interest of serum endocan in the prognosis of COVID-19 [ 21 , 22 , 23 ]. These studies focused on endocan’s ability to predict mortality [ 21 ] and to distinguish moderate from severe degrees of pneumonia [ 22 , 23 ], with different conclusions. While Guzel et al reported that endocan was not associated with the degree of pneumonia [ 22 ], Pascreau et al reported that elevated blood concentrations of endocan may distinguish moderate from severe acute respiratory distress syndrome during COVID-19 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, 48 articles were excluded due to various reasons, while one was added by reference searching, as described in Figure 1. Finally, eight studies, [11][12][13][14][15][16][17][18] including 686 cases, were included in the systematic review. A detailed flowchart of the search and selection process is shown in Figure 1.…”
Section: Literature Search and Characteristics Of Included Studiesmentioning
confidence: 99%